Lived experience research as a resource for recovery: a mixed methods study - Anne Honey; Katherine M. Boydell; Francesca Coniglio; Trang Thuy Do; Leonie Dunn; Katherine Gill; Helen Glover; Monique Hines; Justin Newton Scanlan; Barbara Tooth (BMC Psychiatry, 2020)
Abstract Background Lived experience research is conducted by people who have experience of mental health issues and is therefore better placed than more traditional research to illuminate participants’ experiences. Findings that focus on identifying enablers of recovery from a lived experience perspective have the potential to assist people in their recovery process. However, this lived experience research is often difficult to find, access and interpret. We co-produced user-friendly and engaging resources to disseminate findings from six lived experience research studies. This paper seeks to answer the research questions: a) Did exposure to lived experience research increase hopefulness for participants?; and b) How else did interacting with lived experience research resources influence participants’ lives? Methods Thirty-eight participants were introduced to four resources of their choosing by peer workers over a four-week period. The helpfulness of resources was evaluated using mixed methods, including a quasi-experimental analysis of change in hope, an anonymous survey and in-depth interviews. Results Findings indicated that the resources promoted hope, but that increases in hopefulness may not be seen immediately. Other impacts include that the resources: encouraged helpful activities; provided a positive experience; increased valued knowledge; encouraged people to reflect on their journey and think constructively about mental health issues; helped people to feel less alone; and assisted people to explain their situation to others. Conclusions The research suggests the potential usefulness of lived experience research resources, presented in user-friendly formats, in the lives of people who experience mental health issues and implies a need to nurture this type of research.